2016
DOI: 10.1175/jamc-d-16-0143.1
|View full text |Cite
|
Sign up to set email alerts
|

The Observation Record Length Necessary to Generate Robust Soil Moisture Percentiles

Abstract: The ability to use in situ soil moisture for large-scale soil moisture monitoring, model and satellite validation, and climate investigations is contingent on properly standardizing soil moisture observations. Percentiles are a useful method for homogenizing in situ soil moisture. However, very few stations have been continuously monitoring in situ soil moisture for 20 years or more. Therefore, one challenge in evaluating soil moisture is determining whether the period of record is sufficient to produce a stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Despite SMAP L3 having the best match with the daily variability of in situ θ a , the SMAP distribution of daily θ a values is considerably smaller than that of the NLDAS‐2 and CPC models. The data record length is imperative for the stability of soil moisture percentiles based on that record (i.e., Ford et al, ), and therefore, the shorter SMAP data record enhances daily percentile variability and reduces the effectiveness of the SMAP product for identifying drought severity based on soil moisture percentiles. Concurrently, the data record length of in situ observations impacts the stability of in situ soil moisture percentiles as well.…”
Section: Resultsmentioning
confidence: 99%
“…Despite SMAP L3 having the best match with the daily variability of in situ θ a , the SMAP distribution of daily θ a values is considerably smaller than that of the NLDAS‐2 and CPC models. The data record length is imperative for the stability of soil moisture percentiles based on that record (i.e., Ford et al, ), and therefore, the shorter SMAP data record enhances daily percentile variability and reduces the effectiveness of the SMAP product for identifying drought severity based on soil moisture percentiles. Concurrently, the data record length of in situ observations impacts the stability of in situ soil moisture percentiles as well.…”
Section: Resultsmentioning
confidence: 99%
“…For each station, the daily ePDF was based on 21 soil moisture values in Oklahoma (one for each year from 1996–2016) and 15 values in the Texas Panhandle (2002–2016), sample sizes that we determined to be large enough to create a stable sample distribution. Ford et al (2016) previously reported 3 to 6 yr of soil moisture data were required to create stable sample distributions for daily soil moisture data aggregated to the monthly timescale. Because our data were at the daily timescale, we expected that a somewhat longer data record would be needed to create a stable sample distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Because our data were at the daily timescale, we expected that a somewhat longer data record would be needed to create a stable sample distribution. We applied the method of Ford et al (2016) to our daily data and found that, averaged across each station and day of the year, approximately 11 yr of data were required. We therefore concluded that the data record lengths in our study were sufficient to produce reliable ePDFs.…”
Section: Methodsmentioning
confidence: 99%
“…The available 2003–2011 record length of warm‐season observations was assumed sufficient for estimation of SM and LAC statistics of acceptable accuracy (Findell et al, ; Ford et al, ). Analysis of the variations in R and I values for SM‐EF coupling that occur with the progressive inclusion of each year's warm season (Table S1) raises some caveats, however.…”
Section: Analysis Approach Metrics and Observational Lac Resultsmentioning
confidence: 99%